How do you differentiate f(x)=(x^2+4x)*(x^3+2x+1) using the product rule? Calculus Basic Differentiation Rules Product Rule 1 Answer Guilherme N. Dec 31, 2015 Product rule states that for y=f(x)g(x), then (dy)/(dx)=f'(x)g(x)+f(x)g'(x). Explanation: (dy)/(dx)=(2x+4)(x^3+2x+1)+(x^2+4x)(3x^2+2) (dy)/(dx)=(2x^4+4x^3+4x^2+10x+4)+(3x^4+12x^3+2x^2+8x) (dy)/(dx)=5x^4+16x^3+6x^2+18x+4 Answer link Related questions What is the Product Rule for derivatives? How do you apply the product rule repeatedly to find the derivative of f(x) = (x - 3)(2 - 3x)(5 - x) ? How do you use the product rule to find the derivative of y=x^2*sin(x) ? How do you use the product rule to differentiate y=cos(x)*sin(x) ? How do you apply the product rule repeatedly to find the derivative of f(x) = (x^4 +x)*e^x*tan(x) ? How do you use the product rule to find the derivative of y=(x^3+2x)*e^x ? How do you use the product rule to find the derivative of y=sqrt(x)*cos(x) ? How do you use the product rule to find the derivative of y=(1/x^2-3/x^4)*(x+5x^3) ? How do you use the product rule to find the derivative of y=sqrt(x)*e^x ? How do you use the product rule to find the derivative of y=x*ln(x) ? See all questions in Product Rule Impact of this question 1741 views around the world You can reuse this answer Creative Commons License